The EU’s Energy Policy From the Perspective of a Central-Eastern European Country: Hungary - Mádl, Miklós Vilmos (Maastricht 30: A Central European Perspective, 2025)
Despite the fact that two of the fundamental treaties of the European Union, namely the ECSC and the EURATOM, concerned the energy sector, the following decades were characterised by a great deal of reluctance towards strengthening and deepening the community’s role in the sector. This was partially due to the fact that electricity is a particular product: it is challenging to store, its price depends on howit is produced, and most importantly, for those who are dependent on it, it cannot be substituted. Because of these features, the electricity sector of the European states were dominated by vertically integrated state-owned monopolies where the same companies were responsible for generating and distributing electricity. In spite of the difficulties, the liberalisation of the energy sector began in 1996, and four energy packages were adopted, each of which has tried to address the shortcomings of the previous one. In this article, we will focus on the liberalisation of the European electricity sector by first discussing the rough road that led up to the first package; then, we will attempt to give an overview of each of the packages, followed by an elaboration on how these were implemented in the Hungarian legislation. As the extent of the success of the electricity sector liberalisation is a debated topic, we will also touch upon the issue of whether the market opening reached its goals or not, what are the potential barriers and what we can expect in the future. Keywords: EU energy law, electricity, market opening, Hungarian electricity regulation, liberalisation